The role of sleep in regulating structural plasticity and synaptic strength: Implications for memory and cognitive function. (June 2018) - Raven, Frank; Van der Zee, Eddy A.; Meerlo, Peter; Havekes, Robbert
Summary: Dendritic spines are the major sites of synaptic transmission in the central nervous system. Alterations in the strength of synaptic connections directly affect the neuronal communication, which is crucial for brain function as well as the processing and storage of information. Sleep and sleep loss bidirectionally alter structural plasticity, by affecting spine numbers and morphology, which ultimately can affect the functional output of the brain in terms of alertness, cognition, and mood. Experimental data from studies in rodents suggest that sleep deprivation may impact structural plasticity in different ways. One of the current views, referred to as the synaptic homeostasis hypothesis, suggests that wake promotes synaptic potentiation whereas sleep facilitates synaptic downscaling. On the other hand, several studies have now shown that sleep deprivation can reduce spine density and attenuate synaptic efficacy in the hippocampus. These data are the basis for the view that sleep promotes hippocampal structural plasticity critical for memory formation. Altogether, the impact of sleep and sleep loss may vary between regions of the brain. A better understanding of the role that sleep plays in regulating structural plasticity may ultimately lead to novel therapeutic approaches for brain disorders that are accompanied by sleep disturbances and sleep loss.